(untitled) (Tabanque. Revista Pedagógica, 2018)
The music consubstantial to the human being, is an element of interrelation and development that promotes the capacities for the communicative progress in any social field. I value the voice as a basic element of musical expression. In the didactic application of the classroom we will try to guide the natural and evolutive procedure of the sound expression, promoting the maturation of neurophysiological systems and vocal uses in music education in order to provide feedback to the creative expression of child from the voice. Creative proposals based on certain artistic references will be used whose character will allow to assess the sound and musical nature of children.